O Haroldo de Campos transfinito: espírito, signo e matéria num possível (neo)romantismo em A máquina do mundo repensada - Pachito, Ernesto de Souza (2015)
Since Courbet times, many artists tried to suppress metaphysics from the language of arts in general, including poetry. Many of them made this wide and deep movement with a sense of struggle of classes, being marxists or not. In XXth century, many wings of modernism intensified the search for this goal. At the end of the same century, in the turning to XXIst century, Haroldo de Campos wrote his poem A Máquina do mundo repensada (2000) a work where the lyric subject finds himself caught between complementary oppositions that didn't go to a superior term, at the end of the writting. These dualities were not subsumed under any general term. Metaphysics or not? A world constituted only by matter or there would be something more beyond matter? In this work Haroldo de Campos made the historical and philosophical review of practically all cosmology since Ptolomeu to contemporary times. At the end of the poem he is still in a dilemma between an immanent and a transcendental God, or agnosticism. A Máquina do mundo repensada is a construction full of reverberations of sounds and images, these echoes make fields that project themselves and all signs beyond mere phonetic and imagetic matter, and they operate with symbols (in Wolfgang von Goethe's sense) whose semantic field vanishes into uncertainty and infinity. Peirce, his concept of quale-counsciousness, his monism and his sinechism. The possibility and/or the importance of a sense of ethics in arts after so called relativistic post-modernism.